2010
DOI: 10.1007/s11482-010-9098-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Comorbidity on Psychological Well-being Among Older Persons in Northern Peninsular Malaysia

Abstract: Comorbidity is found to be more prevalent among older people and increases the need for health care. This study examined the effects of chronic comorbidity on psychological well-being of elderly people. A cross-sectional, descriptive study among Northern Malaysians was conducted, involving 385 older people aged 60 years and above randomly selected through multistage random sampling. All respondents completed a questionnaire booklet containing sociodemographic characteristics, self reported chronic morbidity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
1
10
0
2
Order By: Relevance
“… 11 , 17 , 40 Multiple studies have found that people in low socioeconomic status and poor living conditions are more susceptible to acquiring chronic medical conditions and poorer health status. 18 , 41 In parallel with previous studies, 23 , 27 older women reported higher rates of past history of hypertension, diabetes mellitus, and depression, which might be associated with increased incidence of stroke. 42 44 Older women are more vulnerable to social risk factors for depression than men.…”
Section: Discussionsupporting
confidence: 75%
“… 11 , 17 , 40 Multiple studies have found that people in low socioeconomic status and poor living conditions are more susceptible to acquiring chronic medical conditions and poorer health status. 18 , 41 In parallel with previous studies, 23 , 27 older women reported higher rates of past history of hypertension, diabetes mellitus, and depression, which might be associated with increased incidence of stroke. 42 44 Older women are more vulnerable to social risk factors for depression than men.…”
Section: Discussionsupporting
confidence: 75%
“…A higher score indicates a higher level of psychological well‐being 49 . This scale has already been found to be a valid measure of psychological well‐being in older Malaysians 51 . Cronbach's α, the most common measure of reliability, for this scale was 0.84.…”
Section: Methodsmentioning
confidence: 80%
“…Across the public health, social epidemiology, psychology, quality of life and health economics literature, there has been a steady growth of interest in studying chronic illnesses and their negative effect on individual well-being in different countries (Fortin et al 2004;Garin et al 2016;Kaneva et al 2018;Mavaddat et al 2014;McDaid et al 2013;Momtaz et al 2010). Besides a strand within this literature which confirms the intuitive idea that experiencing multiple illnesses is worse for individual well-being than having a single illness (Arokiasamy et al 2015;Kaneva et al 2018;McDaid et al 2013;Mavaddat et al 2014;Momtaz et al 2010), there is a separate body of literature emerging which investigates whether and how internal mechanisms of adaptation and adjustment may complicate the relationship between objective and subjective quality of life measures at the level of the individual (Salas and Vigorito 2019). Studies of individuals living with chronic NCDs (Cubí-Mollá et al 2017;Mathew et al 2012;McTaggard-Cowan et al 2011), experiencing persistent pain (McNamee and Mendolia 2014) or coping with disability (Antonak and Livneh 1995;Brickman and Coates 1978;Oswald and Powdthavee 2008) suggest that individuals are able to adapt to their circumstances in ways which attenuate the potential cumulative effect of multiple chronic illnesses.…”
Section: Introductionmentioning
confidence: 99%